Trends and inequalities in stunting in Nepal: a secondary data analysis of four Nepal demographic health surveys from 2001 to 2016 - Nepali, Sajama (BMC Nutr, 2019)
BACKGROUND: The rate of stunting in Nepal is among the highest in the world, which is a major public health problem. The objective of this study was to present data on stunting prevalence according to socio-demographic and geographical circumstances and to determine the impact of those circumstances on the risk of stunting. METHODS: Data from Nepal Demographic and Health Surveys were used with the study population of children under 5 years old. The prevalence of stunting was determined by descriptive analysis and logistic regression analysis was used to determine risk factors for stunting. RESULTS: The prevalence of stunting has declined in overall as well as in all groups and subgroups analysed. The percentage of stunted children from 2001 to 2016 decreased by 18 and 10.7% in the rural and urban areas respectively. The unadjusted analysis depicted association between stunting and children living in rural areas since children living in rural areas had higher odds of being stunted compared to their urban counterparts. However, the association was no longer observed when adjusted for other variables included in this study. Children born to mothers without any education had 2.27 (95% CI 1.70–3.05), 5.222 (95% CI 2.54–10.74), 1.81 (95% CI 0.92–3.55) and 1.92 (95% CI 1.28–2.89) odds of being stunted than those born to mothers with higher education for the year 2001, 2006, 2011 and 2016 respectively in the adjusted analysis. Similarly, children belonging to the poorest wealth quintile had 1.90 (95% CI 1.55–2.33), 1.87 (95% CI 1.36–2.58), 2.47 (95% CI 1.51–4.02) and 4.18 (95% CI 2.60–6.71) odds of being stunted than those belonging to the richest quintile in 2001, 2006, 2011 and 2016 respectively. The association between stunting and wealth quintile depicting children belonging to the poorest and poorer wealth quintile having higher odds of being stunted remain the same in both unadjusted and adjusted analysis. CONCLUSION: At national level, stunting is decreasing in Nepal; however, the prevalence of stunting is different between groups and subgroups analysed. The substantial inequalities in stunting have been preserved. Therefore, special emphasis should be given to vulnerable groups such as children belonging to the poorest and poorer wealth quintile instead of using blanket approach for delivering nutrition interventions. A balanced approach to nutritional inequalities prevalent across different regions and subgroups is required.